Pengaruh Teknik Akupressure Terhadap Nyeri Punggung Pada Ibu Hamil Di Wilayah Puskesmas Jogonalan I Klaten - Niken Tri Sukeksi; Gita Kostania; Emy Suryani (Poltekkes Kemenkes Surakarta, 2018)
Abstract: Acupressure, Back Pain, Pregnancy. Acupressure is effective to relieve back pain in Meridian point. Acupressure technique is done to help pregnant women in relieving complaints in pregnancy such as nausea and vomiting. In labour process, this technique can be an induction of labor, and can reduce anxiety. The purpose is to know the influence of acupressure technique to relieve back pain for pregnant women in Puskesmas Jogonalan I area of Klaten. Research is pre experimental design with one group pretest posttest approach. The population is all pregnant women in Puskesmas Jogonalan I area of Klaten. The population target is all third trimester of pregnant women in Puskesmas Jogonalan I area of Klaten. Technique sampling is purposive sampling with 30 peopole, ang using t-test data analysis. The characteristics of respondents showed that most of them are 20-35 years old, their gestational age are 3137 weeks, their occupation are housewives, and most of them have 2-3 children. Degree of back pain in pregnant women before acupressure as many as 21 people (70%) are in severe pain. Degree of back pain in pregnant women after given acupressure as many as 24 people (80%) are in mild pain. There is influence of acupressure technique to relieve back pain for pregnant women in Puskesmas Jogonalan I area of Klaten (t =9,893; p=0,001<0,05).